Mechanical and Structural Behavior of Reinforced Self Compacting Concrete Beam (International Journal of Innovative Research in Engineering & Management, 2023)
In this study, punching shear of slabs and the flexural and shear behaviour of reinforced concrete  beams were investigated in connection to the type of  concrete (self compacting concrete (SCC) and normal  concrete (NC)), and compressive strength (40 MPa). To achieve these objectives, two beam have been furnished,  tested, and reviewed. First, one consists of SCC beam and  the second one consists of NC beam. We are add admixtures like fly ash and GGBS. According to test  results, for beams that failed in flexure, SCC beams showed  a similar ultimate load to NC beams. When it came to  slender beams collapsing in shear, NC beams showed a 6.75% higher ultimate load than SCC beams for beams ,  whereas beams with fc' 40 MPa showed nearly the same  ultimate load value. The final loads for SCC and NC beams for beams did not differ noticeably. It was discovered that SCC slabs displayed a 17.25% higher ultimate punching shear load than NC slabs for the six geometrically similar  slabs (three slabs made with SCC and three slabs made with  NC of various concrete strengths) thatwere intended to fail in punching shear.
Keywords: Self-Compacting Concrete; Structural Behavior; Flexure; Shear; Punching Shear; Super Plasticizer; Reinforcement